The essentials of total fitness : exercise, nutrition, and wellness - Powers, Scott K. 1950- (Allyn and Bacon, 1997)
This book is about: Understanding health-related fitness and wellness; Fitness evaluation: self-testing; Improving flexibility; Nutrition, health, and fitness; ...